Beta-sitosterol with antimicrobial property from the stem bark of pomegranate (Punica granatum Linn) - C Nweze; H Ibrahim; G.I. Ndukwe (Journal of Applied Sciences and Environmental Management, 2019)
The aim of this research was to isolate and characterize bioactive substances that may be responsible for the ethno medicinal uses of Punica granatum. Phytochemical constituents and characterization led to the isolation of Beta-Sitosterol from the hexane extract of the stem bark of the plant. The structure of the isolated compound was elucidated by spectra data including FTIR, 1D- and 2D-NMR. The compound was active against Salmonella typhi and Escherichia coli with zones of inhibition of 20 and 35 mm respectively which were appreciable with that of the standard. The values of minimum inhibitory concentration (MIC) were as low as 6.25 and 12.5 μg/ml against Salmonella typhi and Escherichia coli respectively.